PENCITRAAN PARPOL ISLAM DALAM SURAT KABAR - Erfina Nurussa’adah (Jurnal Ilmu Komunikasi AKRAB, 2018)
The Islamic Party began to rebuild its image after experiencing many problems. Stumbling on corruption cases is one of the causes of the decline in the electability of Islamic parties. For this reason, through mass media, the Islamic party is now re-gaining public attention. This study aims to examine how the Islamic party is imaged in the Republika and Tempo SKH in the May-October 2012 edition. The research method used is the critical discourse analysis of Teun A. Van Djik's model. Discourse analysis of the Van Dijk model is divided into three research schemes. First is textual, second is social cognition, third is social analysis or social context in which researchers analyze how discourse develops in society, the production process and reproduction of a person or event is described. The results of the research obtained are, the Republika SKH provides a positive image on the news of the Islamic party through macro structure, super structure, and microstructure. While the Tempo SKH is more critical in conducting news related to Islamic parties.